Role of STAT3 in Angiotensin II-Induced Hypertension and Cardiac Remodeling Revealed by Mice Lacking STAT3 Serine 727 Phosphorylation - Zouein, Fouad A. (2013)
STAT3 is involved in protection of the heart provided by ischemic preconditioning. However, the role of this transcription factor in the heart in chronic stresses such as hypertension has not been defined. We assessed whether STAT3 is important in hypertension-induced cardiac remodeling using mice with reduced STAT3 activity due to a S727A mutation (SA/SA). Wild type (WT) and SA/SA mice received angiotensin (ANG) II or saline for 17 days. ANG II increased mean arterial and systolic pressure in SA/SA and WT mice, but cardiac levels of cytokines associated with heart failure were increased less in SA/SA mice. Unlike WT mice, hearts of SA/SA mice showed signs of developing systolic dysfunction as evidenced by reduction in ejection fraction and fractional shortening. In the left ventricle of both WT and SA/SA mice, ANG II induced fibrosis. However, fibrosis in SA/SA mice appeared more extensive and was associated with loss of myocytes. Cardiac hypertrophy as indexed by heart to body weight ratio and left ventricular anterior wall dimension during diastole was greater in WT mice. In WT+ANG II mice there was an increase in the mass of individual myofibrils. In contrast, cardiac myocytes of SA/SA+ANG II mice showed a loss in myofibrils and myofibrillar mass density was decreased during ANG II infusion. Our findings reveal that STAT3 transcriptional activity is important for normal cardiac myocyte myofibril morphology. Loss of STAT3 may impair cardiac function in the hypertensive heart due to defective myofibrillar structure and remodeling that may lead to heart failure.